2019
DOI: 10.1101/649061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exercise does not induce browning of WAT at thermoneutrality and induces an oxidative, myogenic signature in BAT

Abstract: Background and aimExercise training elicits diverse effects on brown (BAT) and white adipose tissue (WAT) physiology in rodents. However, these animals are typically housed below their thermoneutral zone (i.e. 28-32°C). In these conditions, BAT is chronically hyperactive and, unlike human residence, closer to thermoneutrality. Therefore, we set out to determine the effects of exercise training in obese animals at 28°C (i.e. thermoneutrality) on BAT and WAT in its basal (i.e. inactive) state.MethodsSprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Elucidating protein-protein interactions (PPI) is an important step in understanding both communication between proteins following an intervention and the identification of novel signalling pathways. We have previously shown that ribosomal proteins are important hub proteins in PPI networks following exercise training and, in the present study, show that these also respond to YM-178 [9]. Furthermore, these interact with multiple other mitochondrial ribosomal proteins and proteins governing energy metabolism such as mTOR and leptin.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Elucidating protein-protein interactions (PPI) is an important step in understanding both communication between proteins following an intervention and the identification of novel signalling pathways. We have previously shown that ribosomal proteins are important hub proteins in PPI networks following exercise training and, in the present study, show that these also respond to YM-178 [9]. Furthermore, these interact with multiple other mitochondrial ribosomal proteins and proteins governing energy metabolism such as mTOR and leptin.…”
Section: Discussionsupporting
confidence: 64%
“…Next, we analysed a panel of primary thermogenic genes in BAT and PVAT as we have previously shown these two anatomically and developmentally distinct BAT depots exhibit a divergent response to both a brief period of nutrient excess and exercise training [9, 11]. Despite an increase in BAT mass with cold, there was no reduction in thermogenic genes (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the metabolic responses of skeletal muscle and liver by determining the expression of key genes involved in energy metabolism and metabolic serum parameters including acylcarnitines, ketone bodies, and glycemia. We also assessed the effect of the above protocol on (a) serum levels of thyroid hormone, the action of which is known to partially mimic the response to exercise (Aldiss et al, 2019) (Muscedola s.r.l., Milan, Italy). The animals were acclimated to the 28°C housing temperature for 3 weeks, being familiarized with the treadmill (Panlab, Harvard Apparatus).…”
Section: Introductionmentioning
confidence: 99%
“…During obesity and aging, the gradual shift into WAT-like characteristics of PVAT is associated with the alteration of secretome profile, which may lead to vascular dysfunction, arterial remodeling and increase in blood pressure [ 62 , 63 ]. Apart from cold exposure, exercise training has been shown to induce a BAT-like shift and thermogenic response, which is associated with enhanced eNOS expression and reduced oxidative stress in PVAT [ 64 ].…”
Section: Role Of Adipose Tissue In Metabolic and Cardiovascular Hementioning
confidence: 99%